Experience with market-based environmental policy instruments - Robert N. Stavins (Fondazione Eni Enrico Mattei (FEEM), 2002)
Environmental policies typically combine the identification of a goal with some means to achieve that goal. This chapter for the forthcoming Handbook of Environmental Economics focuses exclusively on the second component, the means - the "instruments" - of environmental policy, and considers, in particular, experience around the world with the relatively new breed of economic-incentive or market-based policy instruments. I define these instruments broadly, and consider them within four categories: charge systems; tradable permits; market friction reductions; and government subsidy reductions. Within charge systems, I consider: effluent charges, deposit-refund systems, user charges, insurance premium taxes, sales taxes, administrative charges, and tax differentiation. Within tradable permit systems, I consider both credit programs and cap-and-trade systems. Under the heading of reducing market frictions, I examine: market creation, liability rules, and information programs. Finally, under reducing government subsidies, I review a number of specific examples from around the world. By defining market-based instruments broadly, I cast a large net for this review of applications. As a consequence, the review is extensive. But this should not leave the impression that market-based instruments have replaced, or have come anywhere close to replacing, the conventional, command-and-control approach to environmental protection. Further, even where these approaches have been used in their purest form and with some success, such as in the case of tradable-permit systems in the United States, they have not always performed as anticipated. In the final part of the paper, I ask what lessons can be learned from our experiences. In particular, I consider normative lessons for: design and implementation; analysis of prospective and adopted systems; and identification of new applications.
Keywords: 330; environmental policy; market-based instruments; economic-incentive instruments; Umweltpolitik; Ökosteuer; Emissionshandel; Marktmechanismus; USA; Welt